Synthesis of Furo[3,2-b]pyrrole-5-carboxhydrazides and Their Cu, CO and Ni Complexes - Renata Gašparová; Ján Titiš; Filip Kraic (The Scientific World Journal)
Carboxhydrazides 3 were synthesized by reaction of substituted furo[3,2-b]pyrrole-5-carboxhydrazides 1 with 4-oxo-4H-chromene-2-carboxaldehyde 2 in the presence of 3-methyl-benzenesulfonic acid in ethanol. Carboxhydrazides 3 were used as ligands for synthesis of Cu, Co, and Ni complexes 4.